The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1371/journal.pone.0146700
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy in HIV Rapid Testing among Laboratory and Non-laboratory Personnel in Zambia: Observations from the National HIV Proficiency Testing System

Abstract: BackgroundDespite rapid task-shifting and scale-up of HIV testing services in high HIV prevalence countries, studies evaluating accuracy remain limited. This study aimed to assess overall accuracy level and factors associated with accuracy in HIV rapid testing in Zambia.MethodsAccuracy was investigated among rural and urban HIV testing sites participating in two annual national HIV proficiency testing (PT) exercises conducted in 2009 (n = 282 sites) and 2010 (n = 488 sites). Testers included lay counselors, nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…User errors, incorrectly performing the test procedure or incorrectly interpreting results, defined as human errors, were reported in 25 studies [7,8,11,14,26–28,31,33,34,37,40,42,46,52,54,57,60,65–68,70,72,73]. Errors identified included users having difficulty with specimen collection [14,28,68], performing RDTs [31,73], interpreting test results [10,24,27,30,32,40,42,48,62,65,66,74], reading test results too early [7] and not using the correct reagents/buffer [7].…”
Section: Resultsmentioning
confidence: 99%
“…User errors, incorrectly performing the test procedure or incorrectly interpreting results, defined as human errors, were reported in 25 studies [7,8,11,14,26–28,31,33,34,37,40,42,46,52,54,57,60,65–68,70,72,73]. Errors identified included users having difficulty with specimen collection [14,28,68], performing RDTs [31,73], interpreting test results [10,24,27,30,32,40,42,48,62,65,66,74], reading test results too early [7] and not using the correct reagents/buffer [7].…”
Section: Resultsmentioning
confidence: 99%
“…A study from Zambia found that the accuracy of HIV rapid tests was higher when testing was performed by trained laboratory personnel compared to non-laboratory personnel. 29 In this report, all testing was performed by experienced laboratory personnel under ideal testing conditions; the frequency of false-negative results in the setting of long-term ART suppression may be higher in other settings. In a previous study of children and adolescents who were virally suppressed on ART, the Uni-Gold rapid test performed better than the OraQuick rapid test.…”
Section: Discussionmentioning
confidence: 99%
“…HIV testing in these settings is mostly conducted by community health workers who are generally well trained and highly proficient in HIV testing. However, in a few instances, lower accuracy has been documented among community workers compared to laboratory staff [16]. The performance of rapid HIV testing has also been found to vary with the reference standard used for evaluation.…”
Section: Introductionmentioning
confidence: 99%